Strategi Pengajaran Guru dan Pengaruhnya terhadap Motivasi dan Semangat Belajar Siswa Kelas 6 SDIT As-Sunnah Cirebon - Nurafifah, Anindia Nabillah; Puntri, Ananda Yulika; Maula, Khofifah Amaliyatul (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2024)
This research aims to examine teachers' teaching strategies and their influence on the motivation and enthusiasm for learning of grade 6 students at SDIT As-Sunnah Cirebon. Using qualitative research methods with a narrative approach, this research collected data through observation and interviews with homeroom teachers. The research results show that teachers use various teaching strategies to increase students' enthusiasm for learning, including interactive methods and emotional motivation. External factors such as the family and social environment also play a significant role in influencing students' enthusiasm for learning. This research concludes that the right approach can increase students' enthusiasm for learning, which in turn improves their achievement and quality of learning. The practical implications of this research include recommendations for teachers and schools to develop teaching strategies that are more effective in motivating students.